Implementation and Challenges of Character Education in the Digital Era: A Case Study at Muhammadiyah Pakem Elementary School - Hidayat, Nur; Wibowo, Yusuf Rendi; Salfadilah, Fatonah (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to analyze the implementation and challenges of character education in the digital era in elementary schools. This study uses a qualitative approach with a case study design. Data were obtained through observation, in-depth interviews, documentation, and open-ended questionnaires as supporting data to strengthen qualitative interpretations. Then, they were analyzed using the interactive model of Miles, Huberman, and Saldana. The results show that while character values have been integrated into intracurricular, co-curricular, and daily habits, their effectiveness is still hampered by students' dependence on gadgets, teachers' limited digital literacy (around 61%), and low parental involvement in monitoring technology use (around 25% consistently apply parental controls). The impact of these conditions is reflected in students' weak digital discipline and responsibility. However, adaptive strategies such as the use of value-laden digital media, educational games, and digital ethics reflection activities have shown positive behavioral changes, which, according to field findings, are marked by a significant decrease in incidents of character violations. The implication is that strengthening the digital literacy-based curriculum and developing a more systematic parent-school collaboration model is needed.